Bi-2212/1T-TaS2 Van der Waals junctions: Interplay of proximity induced high-T c superconductivity and CDW order - Ang J. Li; Xiaochen Zhu; G. R. Stewart; Arthur F. Hebard (Scientific Reports, 2017)
Abstract Understanding the coexistence, competition and/or cooperation between superconductivity and charge density waves (CDWs) in the transition metal dichalcogenides (TMDs) is an elusive goal which, when realized, promises to reveal fundamental information on this important class of materials. Here, we use four-terminal current-voltage measurements to study the Van der Waals interface between freshly exfoliated flakes of the high-T c superconductor, Bi-2212, and the CDW-dominated TMD layered material, 1T-TaS2. For highly transparent barriers, there is a pronounced Andreev reflection feature providing evidence for proximity-induced high-T c superconductivity in 1T-TaS2 with a surprisingly large energy gap (~20 meV) equal to half that of intrinsic Bi-2212 (~40 meV). Our systematic study using conductance spectroscopy of junctions with different transparencies also reveals the presence of two separate boson modes, each associated with a “dip-hump” structure. We infer that the proximity-induced high-T c superconductivity in the 1T-TaS2 is driven by coupling to the metastable metallic phase coexisting within the Mott commensurate CDW (CCDW) phase and associated with a concomitant change of the CCDW order parameter in the interfacial region.